Mechanisms of Vasculogenic Mimicry in Ovarian Cancer - Ayala-Domínguez, Lízbeth; Olmedo-Nieva, Leslie; Muñoz-Bello, J. Omar; Contreras-Paredes, Adriana; Manzo-Merino, Joaquín; Martínez-Ramírez, Imelda; Lizano, Marcela (Frontiers in Oncology, 2019)
Solid tumors carry out the formation of new vessels providing blood supply for growth, tumor maintenance, and metastasis. Several processes take place during tumor vascularization. In angiogenesis, new vessels are derived from endothelial cells of pre-existing vessels; while in vasculogenesis, new vessels are formed de novo from endothelial progenitor cells, creating an abnormal, immature and disorganized vascular network. Moreover, highly aggressive tumor cells form structures similar to vessels, providing a pathway for perfusion; this process is named vasculogenic mimicry (VM), where vessel-like channels mimic the function of vessels and transport plasma and blood cells. VM is developed by numerous types of aggressive tumors, including ovarian carcinoma which is the second most common cause of death among gynecological cancers. VM has been associated with poor patient outcome and survival in ovarian cancer, although the involved mechanisms are still under investigation. Several signaling molecules have an important role in VM in ovarian cancer, by regulating the expression of genes related to vascular, embryogenic and hypoxic signaling pathways. In this review, we provide an overview of the current knowledge of the signaling molecules involved in the promotion and regulation of VM in ovarian cancer. The clinical implications and the potential benefit of identification and targeting of VM related molecules for ovarian cancer treatment are also discussed.